Role of Lezgin Folk Riddles in the Structure of Everyday Fairy Tales (Proceedings of Southern Federal University. Philology, 2021)
Aida R. Gasharova (Makhachkala, Dagestan Republic, Russian Federation)The article deals with Lezgi folk riddles. They can be a constituent element of many genres of folklore, although they exist in folk art as an independent genre. The analysis is focused on folk riddles in the “fairy tale” speech, as well as the use of various kinds of “mysterious” elements in the creation of folk tales. The riddle participates in the complication of many fairy tales. The role of the riddle in a fairy tale is controversial. Basically, the function of riddles in a folk tale is entertaining, but their role in fairy tales is also very significant for the formation of the plot. Riddles are firmly entrenched in a number of fairy tales to complicate them. Both folk tales and folk riddles are metaphorical. We study the traditional plots of Lezgi folk tales, in which we find riddles. The purpose of our study is to identify the multi-aspect interdependence of the Lezgin folk riddle as a plot-forming element in various types of fairy tales. Creative imagination often introduces a riddle into the plot of social and everyday tales “about wise answers” (“about guessing”), which most often contain the origins of difficult riddle problems. The relevance of the chosen topic is due to the lack of study of this issue in the Lezgi oral and poetic creativity.Key words: Lezgin folklore, small aphoristic genres of folklore, folk riddles, everyday tales.DOI 10.18522/1995-0640-2021-2-126-132